FAKTOR – FAKTOR YANG MEMPENGARUHI MAHASISWA BERINVESTASI DI PASAR MODAL SYARIAH - Atalla, Rayhan; Syafrida, Ida (Politeknik Negeri Jakarta, 2023)
The purpose of this study is to determine the factors that influence students to invest in the Islamic capital market, especially Islamic stocks, and to view the dominant variables in influencing student interest in investing using the Exploratory Analysis Factor (EFA) method. This study uses the variables of perception, level of financial literacy, income level, and stock performance analysis - market capitalization with a factor of 40 items. This type of research is descriptive and quantitative with data sourced from questionnaires. A total of 228 people were used as research samples based on the purposive sampling method. The analytical method used in this study uses a Validity Test, Reliability Test, and Exploratory Factor Analysis. The calculation results show that of the 40 factors, 14 factors are dominantly influential. The 14 factors are divided into 2 dominant variables: the level of income and perception. The dominant variables are income level, perception, stock performance analysis – market capitalization, and financial literacy level. The lowest rating of this research is the level of financial literacy. It is hoped that there will be a shared responsibility to further improve financial literacy so that sharia investment is more productive. Keywords: sharia stock capitalization financial literacy, income, perception.